(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
It June-September of 2007 the qualitative and quantitative composition of carabids were investigated in annual fodder’s mixture field in vicinity of Bukowina village in Pomeranian province (N Poland, UTM XA83, 17°50’E and 54°25’N). It was trapping 509 specimen belonged to 23 species. The studied carabid assembly had very specific species composition and ecological structure. Was observed 7 dominant species: Calathus fuscipes, Harpalus griseus, Harpalus rufipes, Harpalus calceatus, Poecilus lepidus, Broscus cephalotes and Harpalus froelichii (more than 5% specimen). This assembly is characterized by low species richness, polydomination, high value Shannon and Pielou indexes, and not typical high seasonal activity of “autumn breeders” in first half of June. Possible reasons of such phenomena are soil condition (dry sand soil) and extreme warm winter 2006/2007.